CD31/PECAM-1 impacts engraftment, growth and spread of mantle cell lymphoma cells and positively correlates with extramedullary involvement. Issue 4 (21st March 2021) - Vockova, Petra; Molinsky, Jan; Klanova, Magdalena; Karban, Josef; Spacek, Martin; Havranek, Ondrej; Kupcova, Kristyna; Kazantsev, Dmitry; Trneny, Marek; Klener, Pavel
Abstract: Platelet/endothelial cell adhesion molecule 1 (PECAM-1, CD31) is an immunoglobulin superfamily member expressed on the surface of platelets, leukocytes and endothelial cells. The role of CD31 in biology of lymphomas has not yet been systemically studied. Expression of cell surface CD31 was analyzed by flow cytometry on primary MCL cells isolated from peripheral blood, bone marrow or malignant effusions obtained from 29 newly diagnosed MCL patients. CD31 was significantly more expressed in patients with documented extranodal involvement. Knock-down of CD31 expression in JEKO1 and MINO MCL cell lines hampered their subcutaneous engraftment in immunodeficient mice and prolonged overall survival of intravenously-xenografted animals. In contrast, transgenic overexpression of CD31 accelerated growth of subcutaneous JEKO1 and MINO tumors, shortened overall survival of intravenously-xenografted mice, and resulted in significantly increased frequency of extramedullary murine tissue infiltration Our observations suggest that CD31 facilitate survival and regulate extranodal spread of MCL cells.